Description of the second fossil Baltic amber species of Monotomidae (Coleoptera: Cucujoidea) - Bukejs, Andris; Alekseev, Vitalii I. (Zootaxa, 2015)
Based on a specimen from the Upper Eocene Baltic amber (Kaliningrad Region, Russia), Aneurops daugpilensis sp. nov. is described. The new species is similar to the extant A. convergens (Sharp, 1900) and A. championi Sharp, 1900 distributed in North and Central America, but differs in the larger punctation of pronotum, and shorter and sparser setation of the median plaque on ventrite 1. Aneurops daugpilensis sp. nov. is distinguished from Europs insterburgensis Alekseev, 2014 by having a median plaque on ventrite 1, a larger body size, and distinctly sparser punctation of the forebody.